Condensation Control of Insulated and Uninsulated Concrete Walls in the Periodic Regime: The Case of Edirne - Umarogullari, Filiz; Gedik, Gulay Zorer; Mihlayanlar, Esma (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
Sustainability is the sum of the precautions and conditions necessary to sustain life on earth. The major elements of sustainable design are choice of material and the building's post-construction performance. The most important factor in terms of building management is energy usage. On building envelope sections which are created to provide energy savings, the value of evaluating water vapor movement is often overlooked. Levels of condensation should not exceed the limits specified in the regulations. This is because the condensed water must not harm the building material or dry it out during the evaporation period. However, the thermal resistance of the building material is affected during the process before the drying period. Deterioration of the insulation material over time means that many theoretical level calculations do not reflect the true situation. In addition, due to the fact that the standards of some of these calculations are done in steady state conditions, realistic results cannot be achieved. If special precautions are not taken with regards to this, condensation damage occurs on the building elements. In this study of the climate conditions in Edirne, calculations are made using the computer program WUFI (R) 2D-3 for buildings' most frequently condensed reinforced concrete wall elements. Insulated and uninsulated wall sections are modeled for periodically changing external and constant internal environmental conditions. For comparison purposes, the reinforced concrete walls are calculated, first for non-insulation, and then insulated with different position of isolation. The calculated results obtained from the WUFI (R) 2D-3 program are shown in graphic form.
Keywords: Humidity trasfer; efficient use of energy; heat transfer; building envelope; condensation; Architecture